2020
DOI: 10.1097/tp.0000000000003378
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Antecedent Bariatric Surgery on Liver Transplant Outcomes: A Retrospective Matched Case-control Study

Abstract: Original Clinical Science-Liver Background. Bariatric surgery (BS) may be associated with significant malabsorption and nutritional deficiencies. Methods. Between March 1987 and January 2017, we performed 922 liver transplants (LT) at our institution; 33 had antecedent BS. We matched the BS cohort to LT recipients without BS (1:3 matching) based on exact matching for gender and cancer and inverse variance matching for age, LT body mass index, MELD score, and transplant date. Results. We analyzed outcomes in 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In the study by Idriss et al, 43 although patients with a history of BS were more likely to be listed for transplant than their matched counterparts, the authors found a higher rate of delisting or death on the wait list, attributed to complication from their BS. However, in both studies, RYGB was the most commonly performed procedure, as well as the most likely to have post‐LT complications 42,43 …”
Section: Bariatric Surgery Related In the Peritransplant Periodmentioning
confidence: 97%
See 3 more Smart Citations
“…In the study by Idriss et al, 43 although patients with a history of BS were more likely to be listed for transplant than their matched counterparts, the authors found a higher rate of delisting or death on the wait list, attributed to complication from their BS. However, in both studies, RYGB was the most commonly performed procedure, as well as the most likely to have post‐LT complications 42,43 …”
Section: Bariatric Surgery Related In the Peritransplant Periodmentioning
confidence: 97%
“…[36][37][38][39][40][41] In two retrospective matched cohort studies, patients with a history of bariatric surgery who underwent LT had no difference in hospital length of stay, complication rate, rejection rate, or 1-and 3-year survival compared with patients who underwent LT alone. 42,43 In the study by Idriss et al, 43 although patients with a history of BS were more likely to be listed for transplant than their matched counterparts, the authors found a higher rate of delisting or death on the wait list, attributed to complication from their BS. However, in both studies, RYGB was the most commonly performed procedure, as well as the most likely to have post-LT complications.…”
Section: Bariatric Surgery Related In the Peritransplant Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…A few monocentric series have reported the results of LT in patients with a history of BS, including a small number of patients in each study [7,[15][16][17][18]. The majority of single-center studies did not find significant differences in the outcomes of LT between patients with or without history of BS [7,15,18].…”
Section: Introductionmentioning
confidence: 99%